Do ritual ao espetáculo: ensaio sobre casamento, “juventude” e educação do olhar na cultura da imagem - Teixeira, Elisabete de Freitas (2015)
This research has its main theme the study of the representation forms of the marriage rituals in the modern culture between young people and the spectacularization of these events nowadays. Therefore, it was analysed twenty six marriage photographies collected from the social networks, and, subsequently, broken into three axles entitled: marriage as a way of life, marriage as a product and marriage as a spectacular – promisse of experience. To consolidate this research have been utilized theoretical references from the field of Culture Studies and Semiotic, as well, authors from the field of Arts and Photography. By the means of this analyses, it can be noticed that the marriage ritual has suffered several displacements in the course of time, mainly concerning its value, since the tradition lost its space for the spectacularization for both the ritual and the protagonists, the fiancés . In this context, the images serves as a visibility tool, wich produce representations of the fiancé, the bride and the marriage. In a time where images come to us in a fast pace, they teach, subjectify and shape the youth of today, through an esthetic education of the seeing, interfering in its ways of being and living in the modern days.